S49 Elicitation of disutility values associated with the mode of administration of drugs acting on the prostacyclin pathway in pulmonary arterial hypertension (pah). (15th November 2017) - Davies, EW; Llewellyn, S; Beaudet, A; Kosmas, CE; Doll, H
Abstract : Introduction and Objectives: Pulmonary arterial hypertension (PAH) is a rare, incurable disease associated with decreased life expectancy and a marked impact on quality of life (QoL). There are three classes of drugs available for treatment: endothelin receptor antagonists (ERA), drugs acting on the nitric oxide pathway (riociguat and phosphodiesterase type 5 inhibitors (PDE5i)), and drugs acting on the prostacyclin pathway. The latter have widely different modes of administration – continuous intravenous infusion, continuous subcutaneous infusion, inhaled and oral – which could be associated with varying treatment burden. Health economic evaluations should incorporate the QoL impact of how drugs are administered. This study aimed to elicit societal utility values associated with different routes of administration of drugs acting on the prostacyclin pathway for use in economic evaluations of PAH treatments. Methods: A UK general public sample completed the EQ-5D-5L and valued four health states in Time-Trade Off interviews. The health states (drafted from literature and interviews with PAH experts (n=3) contained identical descriptions of PAH and ERA/PDE5i treatment, but differed in description of prostacyclin treatment administration including: oral (tablets), inhaled (nebulizer), continuous subcutaneous infusion, and continuous intravenous infusion. Results: A total of 150 participants (63% female; mean age 37 years) completed interviews. Utilities are presented as values between 1 and 0, where 1 is equal being in a state of 'full health' and 0 is equal to being dead. The mean (SD) utility for the oral health state was 0.84 (0.16), while the other health states were all significantly lower at 0.73 (0.27) for inhaled (p=0.001), 0.58 (0.31) for subcutaneous (p<0.001), and 0.54 (0.32) for intravenous (p<0.001). Utility differences compared to the oral health state showed that there are disutilities (negative differences) associated with the inhaled, subcutaneous, and intravenous continuous modes of treatment administration. Disutilities were −0.11 for inhaled, −0.26 for subcutaneous, and −0.30 for intravenous administration. Conclusion: The Results demonstrate quantifiable QoL differences between modes of administration of drugs acting on the prostacyclin pathway, so as to allow appropriate reflection of the unique QoL burden within an economic evaluation of drugs for PAH treatment.